Characterization of probiotics isolated from dietary supplements and evaluation of metabiotic-antibiotic combinations as promising therapeutic options against antibiotic-resistant pathogens using time-kill assay - Mona S. El Far; Azza S. Zakaria; Mervat A. Kassem; Eva A. Edward (BMC, 2024)
Abstract Background The global probiotics dietary supplements market size is continuously growing. To overcome probiotics' health concerns, metabiotics are recognized as a safer alternative. Aiming to deal with the escalating antimicrobial resistance, the current work demonstrates synergistic metabiotic-antibiotic combinations against antibiotic-resistant pathogens. Methods The probiotic properties of lactic acid bacteria (LAB) strains isolated from 3 commercial dietary supplements were characterized in vitro. The combinations of the cell-free supernatants (CFS) of selected probiotic strains and conventional antibiotics against Staphylococcus aureus and Escherichia coli clinical isolates were evaluated using the time-kill assay. To our knowledge, the current literature lacks sufficient time-kill assay studies revealing the kinetics of such metabiotic-antibiotic combinations against S. aureus and E. coli. Results Four LAB strains isolated from dietary supplements as well as two reference strains were included in this study. The isolated LAB strains were identified by MALDI-TOF mass spectrometry as follows: P2: Lactobacillus acidophilus, P3: Lactiplantibacillus plantarum, P4: Lacticaseibacillus rhamnosus, and P5: Pediococcus acidilactici. The identification matched with that annotated by the manufacturers, except for P3. The tested strains could resist the acidic environment at pH 3. Excluding P2, the examined strains showed less than 1 log reduction in survivors upon the addition of reconstituted skimmed milk to pepsin at pH 2 and displayed an acceptable tolerance to 0.3% ox-bile. All the strains tolerated pancreatin. The hydrophobicity and autoaggregation capacities ranged between 7-92% and 36-66%, respectively. P2 was excluded owing to its inferior probiotic potential. Although the remaining strains showed excellent growth at 0.2% phenol, their growth was reduced at higher concentrations. L. plantarum and P. acidilactici strains possessed bile salt hydrolysis activity. The time-kill assay revealed promising synergistic activities of the combinations of CFS of L. rhamnosus P4 with either ceftazidime or gentamicin against E. coli and with only ceftazidime against S. aureus, as well as CFS of P. acidilactici P5 and ceftazidime against S. aureus. Conclusions Strict identification and evaluation of the probiotic strains incorporated in dietary supplements is crucial to ensure their safety and efficacy. The CFS of probiotics could be utilized to formulate novel biotherapeutics targeting problematic pathogens. However, future in vivo studies are required to evaluate the appropriate treatment regimen.